EML webinar overview: Topology Optimization — Status and Perspectives. (September 2020) - Sigmund, Ole
Abstract: Since its introduction by Bendsøe and Kikuchi in (1988), topology optimization has developed from a purely academic discipline to the preferred tool for light-weighting structures in automotive, aerospace and other weight conscious industries. Topology optimization solves mechanical and multiphysics design problems allowing the ultimate design freedom, i.e. it determines whether any point (or element) in space should be filled with material or left empty in order to optimize a given objective function while satisfying physical and geometrical constraints. The talk will give an overview of the field, a.o. demonstrated by recent giga-scale applications in aeroplane wing and super-long suspension bridge design. Originally, the approach focused on simple compliance minimization problems but recent works to be discussed have paved the way for solving large scale stress constraint problems with hundreds of millions of constraints as well as large scale buckling problems. We also discuss ways to reduce the CPU time for large scale problems by use of efficient multiscale approaches and knowledge of optimal microstructures. Finally, other directions including design for geometry control and manufacturability, metamaterial design and multiphysics problems will be briefly reviewed. EML Webinar speakers and videos are updated at https://imechanica.org/node/24098 .